2010
DOI: 10.1007/s11418-010-0462-1
|View full text |Cite
|
Sign up to set email alerts
|

Seven new dammarane triterpenes from the floral spikes of Betula platyphylla var. japonica

Abstract: Seven new dammarane-type triterpenoids, including two 20(S)-hydroxy-25-methoxy-dammar-23-enes (1 and 2), two 20(S),24(R)-epoxydammaranes (3 and 4), a cabralealactone (5), and two 20(S),25-epoxydammaranes (6 and 7), together with seven known triterpenes (8-14), were isolated from the floral spikes of Betula platyphylla var. japonica. The structures for all compounds were elucidated by the analyses of extensive spectroscopic data, as well as chemical examinations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 17 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…However, it has recently been found that mineralized matrixembedded chondrocytes and osteocytes are critical sources of RANKL, which controls osteoclastic resorption in adult bone remodeling. 20) Thus, further studies on the effect of MK on RANKL expression in these cells might provide better understanding of its inhibitory effect.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has recently been found that mineralized matrixembedded chondrocytes and osteocytes are critical sources of RANKL, which controls osteoclastic resorption in adult bone remodeling. 20) Thus, further studies on the effect of MK on RANKL expression in these cells might provide better understanding of its inhibitory effect.…”
Section: Discussionmentioning
confidence: 99%
“…In order to complete and enrich the resource investigation of DTT, we summarize the literatures (1965–2016) describing this type of triterpenoids, extracted from various botanicals. In Table 1, 136 species, from Araliaceae, Cucurbitaceae, Rhamnaceae, and Meliaceae families, together with 42 others are summarized [4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,…”
Section: Plant Resources Of Dttmentioning
confidence: 99%
“…2) (Freysdottir et al 2011;Grundemann et al 2011;Huh et al 2011). A number of new biologically active compounds have recently been isolated, especially from Asiatic birch (Phan et al 2011;Xiong et al 2011). Secondly, birch pollen causes allergy.…”
Section: Birch (Betula L)mentioning
confidence: 99%